(untitled) (Journal of the College of Basic Education, 2022)
Hasan Mudarres was considered an example of a personality who wanted to save a society suffering from oppression and deprivation, and a country suffering from foreign domination. He . was also the right man to stand up to Reza Shah. For over a century, the words of Hassan Mudarres have remained a source of radiation, illuminating the ideas of generations and generations of Iranians, and instilling in the minds the inevitability of establishing an Islamic government and lifting oppression and tyranny from people, and his famous saying is still:(( Our religion is the same as our politics, and our politics is the same as our religion)), an immortal that reflects the essence of faith. It is the words of a religious scholar at the beginning of the twentieth century, and in the period of, such as the two Tebak revolutions in 1890 and the (conditional) constitutional revolution in Iran in 1905, and the Twentieth Revolution in Iraq in 1920, and between the secular Islamic movements, uprisings and revolutions in The years that followed his era, in which the Islamic Republic of Iran was one of its fruits. .